2021
DOI: 10.1016/j.sjbs.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the CNS anti-depressant, antioxidant and cytotoxic profiling of methanol and aqueous extracts of Trametes versicolor and molecular interactions of its phenolic compounds

Abstract: The present study sought to evaluate the central nervous system (CNS) depressant, antioxidant, and cytotoxicity activity of methanol and aqueous extract of Trametes versicolor (METV and AETV). The CNS activity was assessed by the open field, hole-cross, forced swimming, thiopental sodium-induced sleeping time, hole-board, and rotarod tests in Swiss albino mice. For both extracts, a substantial decrease in locomotion was observed in open field and hole-cross tests. In addition, the molecular docking study has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
3
0
3
Order By: Relevance
“…In addition, we showed that TVH may improve the antioxidant protection system by increasing SOD and CAT activity and GSH level. The antioxidant properties of T. versicolor have been confirmed in several studies, however, mostly by using in vitro methods [ 37 , 38 , 39 , 40 , 41 ]. Two studies conducted by Janjusevic et al revealed that T. versicolor is a potential source of antiradical agents, and highlighted the superior ability of aqueous TVH extract to neutralize DPPH • and • OH radicals compared to ethanolic and methanolic TVH extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that TVH may improve the antioxidant protection system by increasing SOD and CAT activity and GSH level. The antioxidant properties of T. versicolor have been confirmed in several studies, however, mostly by using in vitro methods [ 37 , 38 , 39 , 40 , 41 ]. Two studies conducted by Janjusevic et al revealed that T. versicolor is a potential source of antiradical agents, and highlighted the superior ability of aqueous TVH extract to neutralize DPPH • and • OH radicals compared to ethanolic and methanolic TVH extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Những nghiên cứu trên thế giới gần đây khẳng định hệ sợi hay quả thể nấm Vân chi đều có khả năng chống oxy hóa thông qua khử gốc tự do diphenylpicryhydrazyl (DPPH). Tuy nhiên, kết quả thu được về hoạt nh chống oxy hóa của nấm Vân chi khá khác nhau [7][8][9][10][11][12][13]. Theo nghiên cứu của Hossen và cộng sự (2021) khả năng khử gốc tự do DPPH của dịch chiết nấm Vân chi trong dung môi methanol và nước có IC90 lần lượt là 178,83 µg/ml và 518,06 µg/ml [7], nghiên cứu của Ljiljana và cộng sự (2018) cho thấy khả năng chống oxy hoá của dịch chiết nấm Vân chi bằng dung môi enthanol, methanol và nước lần lượt là IC50 = 155,61 µg/ml, 51,57 µg/ml và 14,89 µg/ml [8]; khả năng chống oxy hóa ABTS với IC50 = 8,46 mg/ml [9].…”
Section: đặT Vấn đềunclassified
“…Tuy nhiên, kết quả thu được về hoạt nh chống oxy hóa của nấm Vân chi khá khác nhau [7][8][9][10][11][12][13]. Theo nghiên cứu của Hossen và cộng sự (2021) khả năng khử gốc tự do DPPH của dịch chiết nấm Vân chi trong dung môi methanol và nước có IC90 lần lượt là 178,83 µg/ml và 518,06 µg/ml [7], nghiên cứu của Ljiljana và cộng sự (2018) cho thấy khả năng chống oxy hoá của dịch chiết nấm Vân chi bằng dung môi enthanol, methanol và nước lần lượt là IC50 = 155,61 µg/ml, 51,57 µg/ml và 14,89 µg/ml [8]; khả năng chống oxy hóa ABTS với IC50 = 8,46 mg/ml [9]. Nồng độ dịch chiết quả thể 125 mg/ml có khả năng ức chế gốc tự do DPPH từ 10,97% -22,42% [10], ở nồng độ 1,66 mg/ml -6,66 mg/l cho tỷ lệ ức chế DPPH từ 7,3-20,5% với IC50 là 18,1 mg/ml [11].…”
Section: đặT Vấn đềunclassified
See 1 more Smart Citation
“…Using an autobox ligand, a grid box with an active site in the center was built. BIOVIA Discovery Studio Visualizer 2020 [58] and Pymol 2.6 (Schrödinger LLC., New York, USA) was eventually accelerated to evaluate the docking sites for the potential linking approaches.…”
Section: In Silico Studiesmentioning
confidence: 99%